Simulasi Sistem Dinamis Produksi Tape Ketan - Wijaya, Wijaya; Aisyah, Siti; Nur, Subandi; Mardatila, Farida (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to find out what factors shape the production system of the sticky tape business, and find out how to model the dynamic system of the sticky tape business for the next 10 months. The research data were obtained from interviews with respondents who owned sticky tape businesses. Based on the research results, there are three sub-systems in the sticky tape production system, namely the raw material sub-system and raw material costs, the production sub-system and the sales value (receipt) sub-system, income and business feasibility. Dynamic system modeling in the sticky tape business for the next 10 months is carried out using a scenario approach without improvement and scenario with improvement. The average income per month in the scenario without improvement is Rp. 12,996,269, - and a scenario with an improvement of Rp. 17,200,732,-,- with a feasibility value in the scenario without improvement of 1.84 and the scenario with improvement of 2.01.Keywords : Simulation, Dynamic, Business, Sticky, Tape